Studies on lipovitellin in the back water shrimp Caridina nilotica (Roux, 1833) - Thangaraj, M; Vincent, S G Praksh; Subaja, P K; Savio, V Delphin; Bhimbac, B Valentin (Indian Journal of Fisheries, 2011)
Based on the morphological appearance, ovary of Caridina nilotica was segregated as four maturation stages (I to IV). The biochemical parameters were significantly varied during maturation. Vitellin was quantified from non-denatured PAGE and noted that it positively increased during the ovarian developmental stages. This protein was considered as a lipoglyco nucleic acid binding protein based on specific staining.